2009
DOI: 10.1097/qad.0b013e328328f789
|View full text |Cite
|
Sign up to set email alerts
|

Greater decrease in bone mineral density with protease inhibitor regimens compared with nonnucleoside reverse transcriptase inhibitor regimens in HIV-1 infected naive patients

Abstract: BMD was impaired in 34% of patients, before starting any antiretrovirals. After 1 year, the decrease in lumbar spine BMD was more pronounced in patients receiving either PI/r-containing regimen compared with NNRTI and NRTIs. BMD at specific sites should be monitored during lifelong antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
170
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 38 publications
11
170
2
5
Order By: Relevance
“…Some antiretroviral drugs are also known to accelerate osteoporosis. In countries other than Japan, protease inhibitors (PIs) and TDF/FTC have been reported to decrease bone density compared with other types of antiretroviral drugs (10,11). Changes in bone density were not investigated in the present study, but the long-term effects of RAL and ABC/3TC on bone metabolism should be analyzed further among Japanese patients.…”
Section: Discussionmentioning
confidence: 84%
“…Some antiretroviral drugs are also known to accelerate osteoporosis. In countries other than Japan, protease inhibitors (PIs) and TDF/FTC have been reported to decrease bone density compared with other types of antiretroviral drugs (10,11). Changes in bone density were not investigated in the present study, but the long-term effects of RAL and ABC/3TC on bone metabolism should be analyzed further among Japanese patients.…”
Section: Discussionmentioning
confidence: 84%
“…We were not able to analyse the potential influence of nonnucleoside reverse transcriptase inhibitors (NNRTIs) as this class was represented in both arms. Randomized studies with NNRTI-sparing arms have shown similar or more pronounced BMD decreases following HAART in this arm compared with the NNRTI-containing arm, which argues against the possibility that the process is driven mainly by NNRTIs [6,17]. …”
mentioning
confidence: 99%
“…15 Prospective studies of HIV-infected individuals initiating ART have shown a bone loss of between 2 and 6% in the hip and spine during the first 1-2 years of treatment. [16][17][18][19][20][21][22][23] Tenofovir-containing regimens have consistently been shown to be associated with the greatest bone loss, [20][21][22][23] and in one study the use of PIs was associated with greater bone loss in the spine, 18 although this finding has not been universal. ARTinduced bone loss is accompanied by increases in biochemical markers of bone resorption and formation, implicating increased bone turnover as the mechanism of bone loss.…”
Section: Bmd In Hiv-positive Individualsmentioning
confidence: 80%